Morphological Changes In The Liver In Steatosis Induced By The Use Of Burdock Root (Arctium Lappa) Extract: An Experimental Study (Texas Journal of Medical Science, 2025)
The aim of the study was to investigate morphological changes in the liver during experimental steatosis and to evaluate the corrective effect of burdock root (Arctium lappa) extract. Steatosis was induced in laboratory animals using a high-fat diet combined with the hepatotoxic action of thioacetamide. Morphometric and histological examinations revealed pronounced fatty infiltration, ballooning degeneration of hepatocytes, inflammatory infiltration, and signs of early fibrosis. Administration of A. lappa extract led to a reduction in the degree of steatosis, decreased inflammation, and restoration of the lobular architecture of the liver. The findings indicate the promising potential of burdock root as a natural hepatoprotective agent.